Value of serum and induced sputum surfactant protein-D in chronic obstructive pulmonary disease - Akinci Ozyurek, Berna; Sarinc Ulasli, Sevinc; Savas Bozbas, Serife; Bayraktar, Nilufer; Akcay, Sule (Multidisciplinary Respiratory Medicine, 2013)
Background: Surfactant Protein D (SP-D) is an important marker in chronic obstructive pulmonary disease (COPD). Serum SP-D levels increase while lung production of SP-D decreases in COPD. SP-D is a specific biomarker for monitoring COPD, assessment of exacerbation frequency and arrangement of treatment modalities. In the present study, we aimed to investigate the correlation between serum and induced sputum SP-D levels with severity and acute exacerbations of COPD. Method: 20 healthy subjects, older than 40 years, with at least 10 pack/years smoking history (group 1), 20 stage I-II COPD patients (group 2) , and 20 stage III-IV COPD patients (group 3) were enrolled in the study. All subjects performed pulmonary function tests. Venous blood samples were taken to determine complete blood count, C-reactive protein(CRP) and serum SP-D levels. Induced sputum samples were obtained to determine SP-D level. COPD patients were followed up for acute exacerbations for 6 months. Results: Serum SP-D levels of group 3 were the highest and induced sputum SP-D levels of group 2 were the lowest among the three groups. SP-D levels of induced sputum decreased in patients with increasing number of cigarette pack/years (p = 0.03, r = −0.115), whereas serum SP-D levels increased in these patients (p = 0.0001, r = 0.6 ). Induced sputum SP-D levels in COPD patients receiving inhaled corticosteroid treatment were significantly higher than in patients who were not receiving inhaler corticosteroid treatment (p = 0.005). An inverse correlation between serum SP-D levels and FEV1 (%) was found and there was a positive correlation between the serum SP-D levels and exacerbations frequency in 6-month follow up period (p = 0.049 ,r = −0.252; p = 0.0001, r = 0.598 respectively). Conclusion: Our study demonstrates the adverse effects of smoking on local SP-D levels since low levels of induced sputum SP-D were found in the group of current smokers, who were not receiving inhaled corticosteroid treatment. Relationship between serum SP-D and COPD exacerbations frequency suggests that serum SP-D level may be used as a lung-specific biomarker during the follow up and progression of COPD.